1993
DOI: 10.1095/biolreprod49.4.779
|View full text |Cite
|
Sign up to set email alerts
|

Human Recombinant Inhibin a Suppresses Plasma Follicle-Stimulating Hormone to Intact Levels but has No Effect on Luteinizing Hormone in Castrated Rams1

Abstract: This study tested the hypothesis that inhibin is a major negative feedback regulator of FSH secretion but has minimal effects on LH secretion in rams. In experiment 1, castrated rams (wethers) were given either vehicle or human recombinant inhibin A (hr-inhibin) as three s.c. or three i.v. 50-micrograms injections 6 h apart or as one 50-micrograms i.v. injection followed by 100-micrograms infusion over 12 h. Human recombinant inhibin suppressed plasma FSH while the vehicle had no effect. The greatest suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 44 publications
0
15
0
3
Order By: Relevance
“…The most compelling evidence that inhibin is an important feedback regulator of FSH secretion in male ungulates has come from experiments in which castrated rams have been administered human recombinant inhibin (hr-inhibin) A. In particular, when castrated rams were infused for 12 h with a dose of hr-inhibin A that resulted in the plasma inhibin concentrations found in intact rams, the plasma concentrations of FSH were reduced to values similar to those found in intact rams [89]. This result was achieved without any effect on LH secretion [89].…”
Section: Regulation Of Fsh Secretion By Inhibinmentioning
confidence: 99%
“…The most compelling evidence that inhibin is an important feedback regulator of FSH secretion in male ungulates has come from experiments in which castrated rams have been administered human recombinant inhibin (hr-inhibin) A. In particular, when castrated rams were infused for 12 h with a dose of hr-inhibin A that resulted in the plasma inhibin concentrations found in intact rams, the plasma concentrations of FSH were reduced to values similar to those found in intact rams [89]. This result was achieved without any effect on LH secretion [89].…”
Section: Regulation Of Fsh Secretion By Inhibinmentioning
confidence: 99%
“…The role of inhibin in regulating the production and secretion of FSH has been extensively documented in sheep, both in vivo (Martin et al 1988, Mann et al 1992, Tilbrook et al 1993 and in vitro (Clarke et al 1993, Muttukrishma & Knight 1994. The patterns of secretion of inhibin into the circulation, however, is less clear, due to limitations in the assays employed for its measurement.…”
Section: Introductionmentioning
confidence: 99%
“…inhibin available in sufficient quantities, confirmed the inhibin-induced suppression of FSH secretion in adult rhesus monkeys (Ramaswamy et al, 1998) and rams (Tilbrook et al, 1993a) through a direct action at the pituitary (Tilbrook et al, 1993b). Furthermore, studies in castrated rams have indicated that inhibin acts synergistically with testosterone to maintain the normal feedback regulation of FSH secretion (Tilbrook and Clarke, 2001).…”
Section: Introductionmentioning
confidence: 72%